Improve and extend applied field of the method of distance - frequency Rate - identification in analyzing and processing the aero - geophysical data - Bình, Nguyễn Xuân; Vinh, Nguyễn Đức; Quỳnh, Võ Thanh (Vietnam Journal of Earth Sciences, 2013)
The methods of identification play an important role in analyzing and processing the geophysical data, especially in processing the aero-geophysical data for exploration and prediction of perspective of mineral resources. At the present in geophysics, there are many modern methods of identification that were automated by a lot of powerful professional software and were applied effectively in analyzing aero-geophysical data in Viet Nam and in the world. One of the new methods of identification that were applied effectively in Vietnam is the method of distance-frequency rate-identification which was built by Vo Thanh Quynh. When the method was used for processing the aero-geophysical data, there are some limits needing to be studied and solved. Following this direction we have studied, improved, widened applied field and built new software for method of distance-frequency rate-identification. These new researching results have been applied effectively in analyzing and processing the aero-geophysical data to make clear perspective of mineral resources in the east Tuy Hoa zone.